Kebijakan Transmigrasi di Kabupaten Bengkulu Utara: Perspektif Integrasi Sosial dan Transplantasi Kultural - Heru Susetyo; Satrio Alif Febriyanto; Deden Ardiansyah; Tien Tis’aini Latifah; Feymi Angelina; Ibrahim Ghifar Hamadi; Najma Izzatul Haq; M. Nurrobby Fatih (UNIB Press, 2024)
As one of the countries with the highest population in the world, Indonesia has an uneven population density in each region. This condition encouraged the creation of a transmigration policy to create an equal distribution of population density, which has been carried out since the Dutch East Indies colonial period. The transmigration policy transfers the population from areas with high population density to regions with low population density, equipped with land ownership, public facilities, and agricultural capital goods. The transmigration target area has a local population that has been settled for a long time, so there is interaction between the local population and transmigrants as immigrants. This interaction creates new forms of culture in accommodation and assimilation between the cultures of the local population and migrants. However, this interaction does not always positively impact the relationship between the local population and transmigrants because of the local community's resistance to transmigrants as migrants who are considered to pose a threat to the existence of the local population. The problem will be studied in this research using the socio-legal research method with North Bengkulu Regency as the object of research location to understand the pattern of interaction between residents and transmigrants and its impact on cultural formation through field observations to transmigration areas in North Bengkulu Regency and interviews with residents and transmigrants. This research employs Social Integration Theory of Emile Durkheim and the Cultural Transplant theory of Garett Jones. Based on field data and analysis that has been conducted, the relationship between residents and transmigrants runs harmoniously without any conflict between residents while relatively maintaining their respective cultures. However, some habits of transmigrant communities are followed by residents, and there is disappointment among local communities due to the relocation of public facilities after the transmigration policy. Keywords: Transmigration Policy, Bengkulu Utara; Accommodation; Resistance; Local Community